Aluminum alloy material and hydrogen embrittlement inhibitor for aluminum alloy material
By using Al7Cu2Fe particles as hydrogen traps in specific alloy compositions, the issue of hydrogen embrittlement in aluminum alloys is effectively addressed, improving material resistance for aerospace and space applications.
Patent Information
- Application Number
- JP2024197120
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing aluminum alloy materials do not adequately prevent or suppress hydrogen embrittlement, particularly in applications requiring high levels of resistance such as the aircraft and space industry.
Incorporating specific alloy compositions with second phase particles, specifically Al7Cu2Fe particles, which act as hydrogen traps with higher energy than semi-coherent precipitate interfaces, to effectively prevent hydrogen embrittlement.
The incorporation of Al7Cu2Fe particles significantly reduces hydrogen embrittlement, particularly pseudocleavage cracking, by concentrating hydrogen at strong trap sites, enhancing material resistance in critical applications.
Smart Images

Figure 2025020369000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum alloy material and an agent for preventing hydrogen embrittlement of an aluminum alloy material. [Background technology]
[0002] Aluminum alloy materials, which have a wide range of applications, have a problem of hydrogen embrittlement cracking, and proposals have been made to solve this problem (see Patent Documents 1 to 4).
[0003] Patent Document 1 describes a steel containing, in mass%, 4.0-6.7% Zn, 0.75-2.9% Mg, 0.001-2.6% Cu, 0.05-0.40% Si, 0.005-0.20% Ti, and 0.01-0.5% Fe, and further containing one or more of 0.01-0.7% Mn, 0.02-0.3% Cr, 0.01-0.25% Zr, and 0.01-0.10% V, with the following content: 1.0%≧Fe+Mn+Cr+Zr+V≧0. The document describes an aluminum alloy material for high-pressure gas containers that has excellent resistance to hydrogen embrittlement, and that has an aluminum alloy composition that satisfies the relationship of Electrical Conductivity (%) ≧ -4.9 × (Fe + Mn + Cr + Zr + V) + 40.0 in relation to the total content of Fe, Mn, Cr, Zr, and V, with the balance being Al and unavoidable impurities, and that has a 0.2% yield strength of 275 MPa or more.
[0004] Patent Document 2 describes an Al-Zn-Mg-Cu based aluminum alloy containing 5.0-7.0% Zn, 1.0-3.0% Mg, 1.0-3.0% Cu, and one or more selected from 0.05-0.3% Cr, 0.05-0.25% Zr, 0.05-0.40% Mn, and 0.05-0.35% Sc in a total amount of 0.05-0.5%, with impurities restricted to 0.25% or less Si and 0.25% or less Fe, with the balance being Al and other unavoidable impurities. The method for producing an aluminum alloy thick plate having excellent strength and ductility is described, in which an ingot is subjected to homogenization treatment by holding the ingot at a temperature in the range of 450-520°C for at least one hour, and then in the process of cooling the ingot, the average cooling rate is regulated to at least 100°C / hr to at least 400°C, and then the ingot is hot-rolled at a temperature in the range of 300-440°C to a plate thickness of 50 mm or more. After that, the ingot is solution-treated, quenched, and artificially aged to obtain a thick plate having a total area ratio of intermetallic compounds having a circle equivalent diameter exceeding 5 μm of 2% or less.
[0005] Patent Document 3 describes a method for producing a high-strength Al-Zn-Mg aluminum alloy forging material with excellent resistance to stress corrosion cracking, in which an aluminum alloy containing 4.5 to 8.5 wt% Zn, 1.5 to 3.5 wt% Mg, 0.8 to 2.6 wt% Cu, and at least one type of Mn, Cr, Zr, V, and Ti, with the balance being Al and impurities, is forged into a forging material having an H-section, and the Fe content in the alloy is restricted to 0.15 wt% or less.
[0006] Patent Document 4 describes a high-strength aluminum alloy for welded structural materials having excellent stress corrosion cracking resistance, which contains 5-8 weight percent Zn, 1.2-4.0 weight percent Mg, more than 1.5 weight percent but not more than 4.0 weight percent Cu, 0.03-1.0 weight percent Ag, 0.01-1.0 weight percent Fe, 0.005-0.2 weight percent Ti, 0.01-0.2 weight percent V, and at least one or more of 0.01-1.5 weight percent Mn, 0.01-0.6 weight percent Cr, 0.01-0.25 weight percent Zr, 0.0001-0.08 weight percent B, and 0.03-0.5 weight percent Mo, with the remainder being aluminum and unavoidable impurities. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2009-221566 A [Patent Document 2] JP 2011-058047 A [Patent Document 3] Special Publication No. 1-025386 [Patent Document 4] Patent No. 2915487 Summary of the Invention [Problem to be solved by the invention]
[0008] However, no aluminum alloy material was known that could effectively prevent or suppress hydrogen embrittlement at a level required for the aircraft and space industries. An object of the present invention is to provide an aluminum alloy material and an agent for preventing hydrogen embrittlement of an aluminum alloy material, which can effectively prevent or suppress hydrogen embrittlement. [Means for solving the problem]
[0009] According to the present invention, it has been found that hydrogen embrittlement can be effectively prevented or suppressed by a hydrogen embrittlement inhibitor for an aluminum alloy material having a specific alloy composition or an aluminum alloy material composed of specific second phase particles, thereby solving the above-mentioned problems. Such an alloy is a novel alloy. In Patent Documents 1 to 4, the Fe content in Alloy No. 7050 of JIS H 4100:2014 "Aluminum and aluminum alloy plate and strip" is higher than the prescribed amount, but all of these are outside the range of the aluminum alloy material of the present invention. For example, the composition of Example 6 in Table 1 of Patent Document 1 is Si: 0.21% by mass and Fe: 0.28% by mass, the composition of Alloy A in Table 1 on page 11 of Patent Document 2 is Si: 0.21% by mass and Fe: 0.28% by mass, the composition of Sample 4 in Table 1 on page 4 of Patent Document 3 is Si: 0.10% by mass and Fe: 0.19% by mass, and the composition of Comparative Alloy 10 in Table 1 on page 4 of Patent Document 4 is Si: 0.10% by mass and Fe: 0.20% by mass, all of which are outside the range of the aluminum alloy material of the present invention. The configuration of the present invention, which is a specific means for solving the above problems, and a preferred configuration of the present invention will be described below.
[0010] [1] An aluminum alloy material having an aluminum alloy composition of any one of the following aluminum alloy compositions (1) to (7): Aluminum Alloy Composition (1) Si: 0.30% by mass or less, Fe: more than 0.35% by mass, Cu: 0.20% by mass or less, Mn: 0.20~0.70% by mass, Mg: 1.0~2.0% by mass, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. Aluminum Alloy Composition (2) Si: 0.12 mass% or less, Fe: more than 0.15 mass%, Cu: 1.5 to 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 to 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 to 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 to 0.16 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum Alloy Composition (3) Si: 0.12 mass% or less, Fe: more than 0.25 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum Alloy Composition (4) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.2 - 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 - 2.9 mass%, Cr: 0.18 - 0.26 mass%, Zn: 5.1 - 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (5) 0.7 mass% < Si + Fe, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 - 1.3 mass%, and further contains Al. Aluminum alloy composition (6) Si: 0.12 mass% or less, Fe: more than 0.12 mass%, Cu: 2.0 - 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 - 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 - 6.7 mass%, Zr: 0.08 - 0.15 mass%, Ti: 0.05 mass% or less, and further contains Al. Aluminum alloy composition (7) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.6 - 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 - 3.1 mass%, Cr: 0.18 - 0.28 mass%, Zn: 6.3 - 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al. [2] The aluminum alloy material according to [1], wherein the aluminum alloy composition is the aluminum alloy composition (3). [3] The aluminum alloy material according to [1] or [2], which contains second-phase particles having a hydrogen trap energy higher than that of the semi-coherent precipitate interface. [4] The aluminum alloy material according to [3], wherein the second-phase particles are Al7Cu2Fe particles. [5] It can prevent hydrogen embrittlement of the aluminum alloy material, A hydrogen embrittlement inhibitor for an aluminum alloy material composed of Al7Cu2Fe particles. [6] The hydrogen embrittlement inhibitor for the aluminum alloy material according to [5], which can prevent hydrogen embrittlement of the aluminum alloy material having the following aluminum alloy composition (A). Aluminum alloy composition (A) Si: 0.40 mass% or less, Cu: 2.6 mass% or less, Mn: 0.70 mass% or less, Mg: 3.1 mass% or less, Cr: 0.30 mass% or less, Zn: 7.3 mass% or less, Ti: 0.20 mass% or less, and further containing Fe and Al. [7] The hydrogen embrittlement inhibitor for an aluminum alloy material according to [5] or [6], which can prevent hydrogen embrittlement of an aluminum alloy material having any one of the following aluminum alloy compositions (1) to (7): Aluminum Alloy Composition (1) Si: 0.30% by mass or less, Fe: more than 0.35% by mass, Cu: 0.20% by mass or less, Mn: 0.20~0.70% by mass, Mg: 1.0~2.0% by mass, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. Aluminum Alloy Composition (2) Si: 0.12 mass% or less, Fe: more than 0.15 mass%, Cu: 1.5 to 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 to 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 to 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 to 0.16 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum Alloy Composition (3) Si: 0.12 mass% or less, Fe: more than 0.25 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum Alloy Composition (4) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.2 to 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 to 2.9 mass%, Cr: 0.18 to 0.26 mass%, Zn: 5.1 to 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum Alloy Composition (5) 0.7 mass% < Si + Fe, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 - 1.3 mass%, and further contains Al. Aluminum alloy composition (6) Si: 0.12 mass% or less, Fe: more than 0.12 mass%, Cu: 2.0 - 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 - 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 - 6.7 mass%, Zr: 0.08 - 0.15 mass%, Ti: 0.05 mass% or less, and further contains Al. Aluminum alloy composition (7) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.6 - 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 - 3.1 mass%, Cr: 0.18 - 0.28 mass%, Zn: 6.3 - 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al. [8] A hydrogen embrittlement inhibitor for the aluminum alloy material according to [5] or [6], which can prevent hydrogen embrittlement of the aluminum alloy material being any one of the following aluminum alloy compositions (A1) - (A7). Aluminum alloy composition (A1) Si: 0.30 mass% or less, Fe: 0.35 mass% or less, Cu: 0.20 mass% or less, Mn: 0.20 - 0.70 mass%, Mg: 1.0 - 2.0 mass%, Cr: 0.30 mass% or less, Zn: 4.0 - 5.0 mass%, V: 0.10 mass% or less, Zr: 0.25 mass% or less, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (A2) Si: 0.12 mass% or less, Fe: 0.15 mass% or less, Cu: 1.5 - 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 - 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 - 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 - 0.16 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (A3) Si: 0.12 mass% or less, Fe: 0.15 mass% or less, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum alloy composition (A4) The composition contains Si: 0.40 mass% or less, Fe: 0.50 mass% or less, Cu: 1.2 to 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 to 2.9 mass%, Cr: 0.18 to 0.26 mass%, Zn: 5.1 to 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (A5) The composition satisfies the following requirements: Si+Fe≦0.7 mass%, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 to 1.3 mass%, and further contains Al. Aluminum alloy composition (A6) Si: 0.12 mass% or less, Fe: 0.12 mass% or less, Cu: 2.0 to 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.05 mass% or less, and further containing Al. Aluminum alloy composition (A7) Si: 0.40 mass% or less, Fe: 0.50 mass% or less, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al. Effect of the Invention
[0011] According to the present invention, it is possible to provide an aluminum alloy material and an agent for preventing hydrogen embrittlement of an aluminum alloy material, which can effectively prevent or suppress hydrogen embrittlement. [Brief description of the drawings]
[0012] [Figure 1]FIG. 1 is a virtual cross-section of a tomography image of the microstructure of the aluminum alloy material (High Fe) of Example 1. [Diagram 2] FIG. 2 is a virtual cross-section of a tomography image of a fracture surface of the aluminum alloy material (High Fe) of Example 1. [Diagram 3] FIG. 3 is a virtual cross section of a tomography image of the aluminum alloy material (Low Fe) of Reference Example 2. [Figure 4] FIG. 4 is a virtual cross section of a tomography image of the fracture surface of the aluminum alloy material (Low Fe) of Reference Example 2. [Diagram 5] FIG. 5 is a schematic diagram of the separation of the η / Al interface by hydrogen trapping. [Figure 6] FIG. 6 is a number line diagram of the hydrogen trapping energy of each microstructure in an aluminum alloy material. [Figure 7] FIG. 7 is a schematic diagram of the crystal structure of an Al7Cu2Fe particle (space group P4 / mnc). [Figure 8] FIG. 8 is a bar graph showing the amount of hydrogen trapped at each site in the aluminum alloy materials of Example 1 (High Fe) and Reference Example 2 (Low Fe). [Figure 9] FIG. 9 is a graph showing the relationship between hydrogen distribution to IMC (Al7Cu2Fe) particles (H at IMC), hydrogen distribution to semi-coherent precipitate interfaces (H at η2), and hydrogen embrittlement (quasi-cleavage fracture) area fraction QCF. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits.
[0014] [Aluminum alloy material] The aluminum alloy material of the present invention has an aluminum alloy composition which is any one of the following aluminum alloy compositions (1) to (7). Aluminum alloy composition (1) Si: 0.30 mass% or less, Fe: more than 0.35 mass%, Cu: 0.20 mass% or less, Mn: 0.20 - 0.70 mass%, Mg: 1.0 - 2.0 mass%, Cr: 0.30 mass% or less, Zn: 4.0 - 5.0 mass%, V: 0.10 mass% or less, Zr: 0.25 mass% or less, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (2) Si: 0.12 mass% or less, Fe: more than 0.15 mass%, Cu: 1.5 - 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 - 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 - 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 - 0.16 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (3) Si: 0.12 mass% or less, Fe: more than 0.25 mass%, Cu: 2.0 - 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 - 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 - 6.7 mass%, Zr: 0.08 - 0.15 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (4) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.2 - 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 - 2.9 mass%, Cr: 0.18 - 0.26 mass%, Zn: 5.1 - 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (5) 0.7 mass% < Si + Fe, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 - 1.3 mass%, and further contains Al. Aluminum alloy composition (6) Si: 0.12 mass% or less, Fe: more than 0.12 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.05 mass% or less, and further containing Al. Aluminum Alloy Composition (7) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al. With this configuration, the aluminum alloy material of the present invention can effectively prevent or suppress hydrogen embrittlement, particularly at a level required for the aircraft and space industries.
[0015] In the past, there have been various discussions about the relationship between metal structure and hydrogen embrittlement. Three methods of controlling the structure have been proposed to prevent hydrogen embrittlement: (i) making the distribution of precipitates on the grain boundaries low-density and coarse, (ii) making the grain boundary inclination angle (twist angle) small (to make a non-recrystallized structure), and (iii) making the crystal grains fine (for example, see Goro Ito, Takehiko Eto, Yoshimitsu Miyagi, and Mikihiro Kanno, "Al-Zn-Mg-based alloys," Light Metals, 38 (1988), pp. 818-839. Note that the table on p. 822 lists Al7Cu2Fe tetragonal as a stable phase). However, the effectiveness of these methods was unclear, and the specific mechanism was also unknown. Although the effectiveness is insufficient, the addition of alloy elements such as zirconium and chromium, which is actually used to prevent hydrogen embrittlement, was based on the above (ii) or (iii).
[0016] In contrast, in the present invention, attention was paid to the fact that the local hydrogen distribution and accumulation behavior in the aluminum alloy material governs hydrogen embrittlement cracking. In particular, attention was paid to the fact that the governing factor of hydrogen embrittlement is hydrogen trapped in precipitates (see Engineering Fracture Mechanics 216 (2019) 106503). Then, by calculating the bond energy between each microstructure of aluminum and hydrogen and calculating the hydrogen distribution in the aluminum alloy material, the amount of hydrogen at the hydrogen trapping site that causes hydrogen embrittlement was quantitatively grasped. On that basis, an aluminum alloy material with a specific alloy composition was found that can effectively prevent or suppress hydrogen embrittlement of aluminum alloys by concentrating hydrogen at a site that can strongly trap hydrogen. In addition, it was found that second phase particles having a higher hydrogen trapping energy than the semi-coherent precipitate interface are used as the hydrogen trapping site. The hydrogen embrittlement preventive agent for the aluminum alloy material of the present invention, which will be described later, is made of Al7Cu2Fe particles having the above-mentioned hydrogen trapping sites. Hydrogen embrittlement cracking includes grain boundary cracking and quasi-cleavage cracking, and the present invention can effectively prevent or suppress quasi-cleavage cracking in particular. Preferred embodiments of the present invention will now be described.
[0017] <Aluminum alloy composition> The aluminum alloy material of the present invention has the aluminum alloy composition of any one of the above-mentioned aluminum alloy compositions (1) to (7). Among these aluminum alloy compositions, in the present invention, the aluminum alloy composition is preferably the above-mentioned aluminum alloy composition (3). In the aluminum alloy material of the present invention, the amount of Fe relative to the entire aluminum alloy material is preferably more than 0.12 mass%, more preferably more than 0.15 mass%, particularly preferably more than 0.25 mass%, and more particularly preferably 0.30 mass% or more. With an increase in the amount of Fe, the volume fraction of second-phase particles (preferably Al7Cu2Fe particles), the number density of the second-phase particles, and the particle size of the second-phase particles can also be increased. On the other hand, there is no particular upper limit for the Fe content. For example, the Fe content relative to the entire aluminum alloy material can be, for example, 1.0 mass% or less, 0.8 mass% or less, or 0.6 mass% or less. When the Fe content is less than these upper limits, the volume fraction, number density, and particle size of the second phase particles can be reduced to some extent, making it easier to suppress deterioration of material properties due to the aggregation and localization of the second phase particles. The aluminum alloy material of the present invention is mainly composed of aluminum, and preferably contains 0.50 mass % or more of aluminum. More preferable ranges of the aluminum alloy composition will be explained in order.
[0018] The aluminum alloy composition (1) is as follows: Si: 0.30% by mass or less, Fe: more than 0.35% by mass, Cu: 0.20% by mass or less, Mn: 0.20~0.70% by mass, Mg: 1.0~2.0% by mass, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. In the aluminum alloy composition (1), Fe: preferably more than 0.35 mass % and not more than 1.0 mass %, and more preferably more than 0.35 mass % and not more than 0.6 mass %.
[0019] The aluminum alloy composition (2) is as follows: Si: 0.12 mass% or less, Fe: more than 0.15 mass%, Cu: 1.5 to 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 to 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 to 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 to 0.16 mass%, Ti: 0.06 mass% or less, and further containing Al. In the aluminum alloy composition (2), Fe: preferably more than 0.15 mass % and not more than 1.0 mass %, and more preferably more than 0.15 mass % and not more than 0.6 mass %.
[0020] The aluminum alloy composition (3) is as follows: Si: 0.12 mass% or less, Fe: more than 0.25 mass%, Cu: 2.0 - 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 - 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 - 6.7 mass%, Zr: 0.08 - 0.15 mass%, Ti: 0.06 mass% or less, and further contains Al. In the aluminum alloy composition (3), it is preferable that Fe is more than 0.25 mass% and 1.0 mass% or less, and more preferably more than 0.25 mass% and 0.6 mass% or less.
[0021] The aluminum alloy composition (4) is as follows. Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.2 - 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 - 2.9 mass%, Cr: 0.18 - 0.26 mass%, Zn: 5.1 - 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. In the aluminum alloy composition (4), it is preferable that Fe is more than 0.55 mass% and 1.0 mass% or less, and more preferably more than 0.55 mass% and 0.6 mass% or less.
[0022] The aluminum alloy composition (5) is as follows. 0.7 mass% < Si + Fe, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 - 1.3 mass%, and further contains Al. In the aluminum alloy composition (5), it is preferable that 0.7 mass% < Si + Fe ≤ 1.0 mass%. Also, it is preferable that Fe is more than 0.35 mass% and 1.0 mass% or less, and more preferably more than 0.35 mass% and 0.6 mass% or less.
[0023] The aluminum alloy composition (6) is as follows. Si: 0.12 mass% or less, Fe: more than 0.12 mass%, Cu: 2.0 - 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 - 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 - 6.7 mass%, Zr: 0.08 - 0.15 mass%, Ti: 0.05 mass% or less, and further contains Al. In the aluminum alloy composition (6), Fe: preferably more than 0.12 mass % and not more than 1.0 mass %, and more preferably more than 0.12 mass % and not more than 0.6 mass %.
[0024] The aluminum alloy composition (7) is as follows: Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al. In the aluminum alloy composition (7), Fe: preferably more than 0.50 mass % and not more than 1.0 mass %, and more preferably more than 0.50 mass % and not more than 0.6 mass %.
[0025] <Alloy material shape> The shape of the aluminum alloy material of the present invention is not particularly limited. The aluminum alloy material may be in the form of a lump or particles, and is preferably in the form of a lump.
[0026] <Second phase particles> The aluminum alloy material of the present invention preferably includes second phase particles that have a higher hydrogen trapping energy than semi-coherent precipitate interfaces. The second phase particles are particles having a different composition from the component composition of the parent phase. The second phase particles of an aluminum alloy material are particles having a different composition from Al or its aluminum alloy material. There is no particular restriction on the second phase particles having a higher hydrogen trapping energy than the semi-coherent precipitate interface. By using first-principles calculations, it is possible to obtain second phase particles having a higher hydrogen trapping energy than the semi-coherent precipitate interface. First-principles calculations refer to theoretically expressing the electronic state by mathematically solving the Schrodinger equation (without using experimental data or empirical parameters). The distribution of hydrogen at each trapping site can be calculated from the density of other hydrogen trapping sites such as grain boundaries, precipitates, and interstitials, and the bond energy with hydrogen. In addition, by observing the deformation process of an aluminum alloy material using synchrotron radiation tomography and performing 3D or 4D image processing, it is possible to track the second phase particles dispersed in the aluminum alloy material and perform 3D mapping of the internal plastic strain distribution. The concentration distribution of geometrically necessary dislocations, statistically necessary dislocations, and atomic vacancies can be calculated from the 3D strain distribution. In the present invention, the second phase grains having a higher hydrogen trapping energy than the semi-coherent precipitate interface are preferably Al7Cu2Fe grains. Note that the grains having an atomic ratio of Al:Cu:Fe that deviates from the stoichiometric composition of 7:2:1 by about 30% (e.g., Al7Cu2Fe 0.7 A similar effect can be expected for Al7Cu2Fe particles. Among the hydrogen trapping energies of the microstructures in aluminum alloy materials, the Al7Cu2Fe particles have a hydrogen trapping energy of 0.56 eV. However, no preferred second phase particles or microstructures other than Al7Cu2Fe particles that have a hydrogen trapping energy higher than the 0.55 eV of the semi-coherent precipitate interface are known yet.
[0027] The second phase particles may have various shapes such as spheres, ellipsoids, square tubes, cylinders, cubes, rectangular parallelepipeds, and scales, and are preferably spheres or ellipsoids.
[0028] The volume fraction of the second phase particles is preferably 0.05 to 10.0%, more preferably 0.1 to 5.0%, and particularly preferably 0.5 to 2.0%. The volume fraction of the second phase particles can be calculated as the volume of the second phase particles relative to the volume of the aluminum alloy material by 3D analysis using, for example, X-ray tomography (CT).
[0029] The number density of second phase particles is 6.5×10 12 / m 3 ~100×10 12 / m 3 Preferably, 10×10 12 / m 3 ~50×10 12 / m 3 More preferably, it is 20×10 12 / m 3 ~40×10 12 / m 3 It is particularly preferable that the number density of the second phase particles is calculated by 3D analysis, for example, by high-resolution X-ray tomography (CT) with a spatial resolution of up to 1 μm.
[0030] The average particle size of the second phase particles is preferably 0.5 to 20 μm. The upper limit of the average particle size of the second phase particles is more preferably 10 μm or less, and particularly preferably 5.0 μm or less. The average particle size of the second phase particles can be calculated as an arithmetic mean by 3D analysis using, for example, X-ray tomography (CT).
[0031] <Method of manufacturing aluminum alloy material> The method for producing the aluminum alloy material is not particularly limited. By forming a hydrogen embrittlement inhibitor for aluminum alloy material made of Al7Cu2Fe particles inside the raw material aluminum alloy material, hydrogen embrittlement of the aluminum alloy material can be prevented. Al7Cu2Fe particles may be added to the raw aluminum alloy material, or Fe may be added during production to form Al7Cu2Fe particles, and the Al7Cu2Fe particles may ultimately be used as a hydrogen embrittlement inhibitor. The raw aluminum alloy material may be a raw material mixture before each metal or metal compound including Al is alloyed.
[0032] The aluminum alloy material can be manufactured by known processes such as heat treatment, rolling, forging and / or casting of the raw aluminum alloy material (which may be a raw material mixture). In the present invention, it is preferable to manufacture the aluminum alloy material by casting the raw aluminum alloy material from the viewpoint of suppressing hydrogen trapping in precipitates, i.e., suppressing quasi-cleavage fracture. In particular, it is preferable to add more Fe to the raw material mixture before each metal or metal compound is alloyed during casting than in the case of manufacturing a conventional aluminum alloy material, thereby actively forming Al7Cu2Fe particles. Also, heat treatment, rolling and forging may not be performed. As for other manufacturing methods, the methods described in
[0034] to
[0042] of JP 2009-221556 A can be used, and the contents of this publication are incorporated herein by reference.
[0033] [Hydrogen embrittlement prevention agent for aluminum alloys] The hydrogen embrittlement preventive agent for aluminum alloy material of the present invention can prevent hydrogen embrittlement of aluminum alloy material and is composed of Al7Cu2Fe particles. Although Al7Cu2Fe particles are sometimes contained in existing aluminum alloy materials, it was not known that they act as an additive to prevent hydrogen embrittlement in aluminum alloy materials.
[0034] <Aluminum alloy raw material> The aluminum alloy material as the raw material for which hydrogen embrittlement is to be prevented may be the aluminum alloy material of the present invention or an existing aluminum alloy material.
[0035] The hydrogen embrittlement inhibitor for an aluminum alloy material of the present invention is preferably capable of preventing hydrogen embrittlement of an aluminum alloy material having the following aluminum alloy composition (A). Aluminum alloy composition (A) Si: 0.40 mass% or less, Cu: 2.6 mass% or less, Mn: 0.70 mass% or less, Mg: 3.1 mass% or less, Cr: 0.30 mass% or less, Zn: 7.3 mass% or less, Ti: 0.20 mass% or less, and further containing Fe and Al.
[0036] When the raw aluminum alloy material to be prevented from hydrogen embrittlement is the aluminum alloy material of the present invention, the hydrogen embrittlement inhibitor for the aluminum alloy material of the present invention can preferably prevent hydrogen embrittlement of the aluminum alloy material having any one of the above-mentioned aluminum alloy compositions (1) to (7).
[0037] When the raw aluminum alloy material to be prevented from hydrogen embrittlement is an existing aluminum alloy material, the hydrogen embrittlement inhibitor for aluminum alloy material of the present invention is preferably capable of preventing hydrogen embrittlement of an aluminum alloy material having any of the following aluminum alloy compositions (A1) to (A7). However, when the raw aluminum alloy material to be prevented from hydrogen embrittlement is an existing aluminum alloy material, it is preferable to make the particle size of the second phase particles smaller and more dispersed than before, so as to make it easier to prevent hydrogen embrittlement. Aluminum alloy composition (A1) Si: 0.30% by mass or less, Fe: 0.35% by mass or less, Cu: 0.20% by mass or less, Mn: 0.20~0.70% by mass, Mg: 1.0~2.0% by mass, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. Aluminum alloy composition (A2) Si: 0.12 mass% or less, Fe: 0.15 mass% or less, Cu: 1.5 to 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 to 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 to 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 to 0.16 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum alloy composition (A3) Si: 0.12 mass% or less, Fe: 0.15 mass% or less, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further containing Al. Aluminum alloy composition (A4) The composition contains Si: 0.40 mass% or less, Fe: 0.50 mass% or less, Cu: 1.2 to 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 to 2.9 mass%, Cr: 0.18 to 0.26 mass%, Zn: 5.1 to 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (A5) The composition satisfies the following requirements: Si+Fe≦0.7 mass%, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 to 1.3 mass%, and further contains Al. Aluminum alloy composition (A6) Si: 0.12 mass% or less, Fe: 0.12 mass% or less, Cu: 2.0 to 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.05 mass% or less, and further containing Al. Aluminum alloy composition (A7) Si: 0.40 mass% or less, Fe: 0.50 mass% or less, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al.
[0038] The aluminum alloy compositions (A1) to (A7) are summarized in the following Table 1. The alloy numbers in Table 1 refer to the alloy numbers in JIS H 4100:2014 "Aluminum and aluminum alloy plate and strip."
[0039] [Table 1] EXAMPLES
[0040] The present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0041] [Example 1] As an aluminum alloy material satisfying the aluminum alloy composition (3), an aluminum alloy material (High Fe) of Example 1 containing 0.30 mass% of Fe was prepared by the following method. This aluminum alloy material is also an Al-Zn-Cu alloy containing 50 mass% or more of Al as a main component, followed by Zn and then Cu. The material for casting aluminum alloy material that satisfies the composition of alloy number 7050 in JIS H 4100:2014 "Aluminum and aluminum alloy plate and strip", i.e., aluminum alloy composition (A3), was further added Fe to the melt to form Al7Cu2Fe particles as second phase particles inside the material.
[0042] [Reference Examples 1 and 2] As aluminum alloy materials satisfying the composition of alloy number 7050 of JIS H 4100:2014 "Aluminum and aluminum alloy plate and strip", i.e., aluminum alloy composition (A3), an aluminum alloy material (Mid Fe) of Reference Example 1 containing 0.05 mass% Fe and an aluminum alloy material (Low Fe) of Reference Example 2 containing 0.01 mass% Fe were prepared.
[0043] [evaluation] <3D analysis> The aluminum alloy materials of Example 1 and Reference Examples 1 and 2 were 3D analyzed by X-ray tomography. The results are shown in Table 2 below. In Table 2 below, particles refer to Al7Cu2Fe particles.
[0044] [Table 2]
[0045] From Table 2 above, it was found that as the Fe content increases, the volume fraction of Al7Cu2Fe particles also increases.
[0046] <Tomography image> Next, tomographic images of the aluminum alloy materials of Example 1 and Reference Examples 1 and 2 were taken. A virtual cross section of a tomography image of the microstructure of the aluminum alloy material (High Fe) of Example 1 is shown in Figure 1. Also, a virtual cross section of a tomography image of the fracture surface of the aluminum alloy material (High Fe) of Example 1 is shown in Figure 2. In Figures 2 and 4, QCF means area fraction of quasi-cleavage creak. A virtual cross section of a tomography image of the aluminum alloy material (Low Fe) of Reference Example 2 is shown in Fig. 3. Moreover, a virtual cross section of a tomography image of a fracture surface of the aluminum alloy material (Low Fe) of Reference Example 2 is shown in Fig. 4. It should be noted that the illustration of Reference Example 1 is omitted.
[0047] From Fig. 1, it was found that second phase particles called Al7Cu2Fe particles were formed inside the aluminum alloy material (High Fe) of Example 1. It was also found that the Al7Cu2Fe particles were present in a highly dense and dispersed state on the order of microns. On the other hand, it was found that in the aluminum alloy material (Low Fe) of Reference Example 2 shown in FIG. 3, second phase particles were hardly formed inside the material.
[0048] 2 and 4, and the results of Reference Example 1 (not shown), the area fraction QCF of the quasi-cleavage fracture surface in Example 1 (High Fe), Reference Example 1 (Mid Fe), and Reference Example 2 (Low Fe) was obtained. The obtained results are shown in Table 3 below.
[0049] [Table 3]
[0050] From Table 3 above, hydrogen embrittlement can be reduced. It was found that the area fraction of quasi-cleavage fracture QCF decreased from 22.4% to 8.1% by increasing the Fe content from 0.01% by mass to 0.3% by mass. Since the area fraction of quasi-cleavage fracture QCF corresponds to the hydrogen embrittlement fracture rate, it was found that hydrogen embrittlement can be reduced by increasing the Fe content more than that of existing aluminum alloy materials, forming Al7Cu2Fe particles as second phase particles inside the material, and dispersing them at a high density on the order of microns. It was also found that Al7Cu2Fe particles can effectively prevent or suppress quasi-cleavage fracture in aluminum alloy materials, and are extremely effective as a hydrogen embrittlement inhibitor for aluminum alloy materials.
[0051] <Analysis of hydrogen distribution> For the aluminum alloy materials of Example 1, Reference Example 1 and Reference Example 2, the hydrogen amount in the microstructure H at IMC and the hydrogen amount in the semi-coherent precipitates (η2, semi-coherent) (H at η2) were calculated by a calculation process.
[0052] (1) Semi-spontaneous delamination of semi-coherent precipitate interfaces by hydrogen The separation of the η / Al interface due to hydrogen trapping was calculated using first-principles calculations, and the results are shown in Figure 5. From Fig. 5, it was found that when hydrogen is concentrated at the semi-coherent precipitate interface (η2, semi-coherent), the interface semi-spontaneously peels off, which becomes the starting point of hydrogen embrittlement. This result is a new mechanism of hydrogen embrittlement in aluminum alloy materials.
[0053] (2) Hydrogen trapping energy of microstructure Using first-principles calculations, the hydrogen trapping energy of each microstructure in an aluminum alloy material was calculated. The results are shown in Figure 6. In Figure 6, from the left, the following are shown: screw dislocation (Screw disl.), solute Mg atom (Solute Mg), edge dislocation (Edge disl.), grain boundary (GB), vacancy (Vac.), coherent precipitate interface (η1, coherent), semi-coherent precipitate interface (η2, semi-coherent), Al7Cu2Fe particle (IMCp), pore surface (Pore(surface H)), and molecular hydrogen in pore (Pore(H2)). From Fig. 6, it was found that in controlling hydrogen embrittlement, structural control by heat treatment or rolling is not effective in suppressing hydrogen trapping in precipitates, i.e., suppressing quasi-cleavage fracture. The binding energy between precipitates and hydrogen is the second highest after pores, and the hydrogen trap site density is also high. In order to suppress quasi-cleavage fracture based on hydrogen distribution control, it is necessary to provide sites in the material that have a higher binding energy with hydrogen than precipitates and a sufficiently high trap site density. From Fig. 6, it was found that of the hydrogen trapping energies of each microstructure, the Al7Cu2Fe particles have a hydrogen trapping energy of 0.56 eV, which is higher than the 0.35 eV of the coherent precipitate interface (η1, coherent) and the 0.55 eV of the semi-coherent precipitate interface (η2, semi-coherent). In other words, the Al7Cu2Fe particles have a higher hydrogen trapping energy than the semi-coherent precipitate interface, which is effective in preventing hydrogen embrittlement. The crystal structure (space group P4 / mnc) of an Al7Cu2Fe particle is shown in Figure 7 (see Bown et al., Acta Cryst., 9 (1956), 911). Figure 7 confirms that there are hydrogen trapping sites inside the Al7Cu2Fe particle that can strongly trap H.
[0054] (3) Calculation of hydrogen distribution state The distribution state of hydrogen in aluminum alloy materials was analyzed. Based on the following equations 1 to 3, the hydrogen distribution state under thermal equilibrium was calculated using the hydrogen trapping energy obtained by first-principles calculation. The specific calculation was performed according to Engineering Fracture Mechanics 216 (2019) 106503.
[0055]
number
[0056]
number
[0057]
number
[0058] The obtained results are shown in FIG. 8. In FIG. 8, the amounts of hydrogen trapped in the microstructures of interstitial (Lattice), solute Mg atoms (Mg), vacancies (V), grain boundaries (⊥), Al7Cu2Fe particles (IMCp), coherent precipitate interfaces (coherent), semi-coherent precipitate interfaces (semi-coherent), and pores are shown from the left to the right. The two bar graphs in each microstructure represent the case where the Fe content is 0.30 mass% (High Fe) corresponding to Example 1 on the left side of the page, and the case where the Fe content is 0.01 mass% (Low Fe) corresponding to Reference Example 2 on the right side of the page. Note that the results in the case where the Fe content is 0.05 mass% (Mid Fe) corresponding to Reference Example 1 are omitted in FIG. 8. As shown in Figure 8, hydrogen in an aluminum alloy is distributed to each microstructure according to the trapping energy. In an aluminum alloy material with a low Fe content of 0.01 mass% (Low Fe) similar to Reference Example 1, hydrogen is most strongly distributed to the interface of semi-coherent precipitates (η2, semi-coherent), which becomes the starting point of hydrogen embrittlement (see Figure 5 above). On the other hand, in an aluminum alloy with a high Fe content of 0.30 mass% (High Fe), similar to that of Example 1, hydrogen is most strongly distributed to Al7Cu2Fe particles (IMCp). This reduces the hydrogen concentration at precipitate interfaces, such as semi-coherent precipitate (η2) interfaces, and prevents hydrogen embrittlement.
[0059] The above evaluation results are summarized in Fig. 9. Fig. 9 is a graph showing the relationship between hydrogen distribution to IMC (Al7Cu2Fe) particles (H at IMC), hydrogen distribution to semi-coherent precipitate interfaces (H at η2), and hydrogen embrittlement (quasi-cleavage fracture) area fraction QCF, etc. The horizontal axis represents the Fe content in the aluminum alloy materials of Example 1, Reference Example 1, and Reference Example 2. Here, from Table 1 mentioned above, it was found that as the amount of Fe in the aluminum alloy material increases, the volume fraction of Al7Cu2Fe particles also increases. From the results in Table 1 and Figure 9, it was found that as the Fe content in the aluminum alloy material increases, the amount of hydrogen trapped by the Al7Cu2Fe particles increases (dashed line; H at IMC), the amount of hydrogen in the precipitates decreases (H at η2), and hydrogen embrittlement (quasi-cleavage fracture) can be effectively prevented or suppressed (QCF). In addition, it was found that the Al7Cu2Fe particles effectively function as a hydrogen embrittlement prevention agent for aluminum alloy materials by forming them as second phase particles inside the material, even when the material is used for casting aluminum alloy materials having a conventionally known composition as specified in JIS H 4100:2014.
Claims
1. An aluminum alloy material, the aluminum alloy composition being any one of the following aluminum alloy compositions (1) to (7). Aluminum alloy composition (1) Si: 0.30% by mass or less, Fe: more than 0.35% by mass, Cu: 0.20% by mass or less, Mn: 0.20 to 0.70% by mass, Mg: 1.0 to 2.0% by mass, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. Aluminum alloy composition (2) The alloy contains 0.12% by mass or less of Si, more than 0.15% by mass of Fe, 1.5 to 2.0% by mass of Cu, 0.10% by mass or less of Mn, 2.1 to 2.6% by mass of Mg, 0.05% by mass or less of Cr, 5.7 to 6.7% by mass of Zn, 0.05% by mass or less of Ni, 0.10 to 0.16% by mass of Zr, and 0.06% by mass or less of Ti, and further contains Al. Aluminum alloy composition (3) The alloy contains Si: 0.12 mass% or less, Fe: more than 0.25 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (4) The alloy contains Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.2 to 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 to 2.9 mass%, Cr: 0.18 to 0.26 mass%, Zn: 5.1 to 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (5) 0.7% by mass<Si+Fe, Cu: 0.10% by mass or less, Mn: 0.10% by mass or less, Mg: 0.10% by mass or less, Zn: 0.8 to 1.3% by mass, and further containing Al. Aluminum alloy composition (6) The alloy contains Si: 0.12 mass% or less, Fe: more than 0.12 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.05 mass% or less, and further contains Al. Aluminum alloy composition (7) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al.
2. 2. The aluminum alloy material according to claim 1, wherein the aluminum alloy composition is the aluminum alloy composition (3).
3. 3. The aluminum alloy material of claim 1 or 2, comprising second phase particles having a higher hydrogen trapping energy than semi-coherent precipitate interfaces.
4. The second phase particles are Al 7 Cu 2 The aluminum alloy material according to claim 3, which is an Fe particle.
5. It can prevent hydrogen embrittlement of aluminum alloy materials, A 7 Cu 2 An agent for preventing hydrogen embrittlement of aluminum alloy materials, comprising Fe particles.
6. 6. The hydrogen embrittlement inhibitor for aluminum alloy material according to claim 5, which can prevent hydrogen embrittlement of an aluminum alloy material having the following aluminum alloy composition (A). Aluminum alloy composition (A) Si: 0.40 mass% or less, Cu: 2.6 mass% or less, Mn: 0.70 mass% or less, Mg: 3.1 mass% or less, Cr: 0.30 mass% or less, Zn: 7.3 mass% or less, Ti: 0.20 mass% or less, and further containing Fe and Al.
7. The hydrogen embrittlement inhibitor for aluminum alloy material according to claim 5 or 6, which can prevent hydrogen embrittlement of an aluminum alloy material having any one of the following aluminum alloy compositions (1) to (7). Aluminum alloy composition (1) Si: 0.30% by mass or less, Fe: more than 0.35% by mass, Cu: 0.20% by mass or less, Mn: 0.20 to 0.70% by mass, Mg: 1.0 to 2.0% by mass, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. Aluminum alloy composition (2) The alloy contains 0.12% by mass or less of Si, more than 0.15% by mass of Fe, 1.5 to 2.0% by mass of Cu, 0.10% by mass or less of Mn, 2.1 to 2.6% by mass of Mg, 0.05% by mass or less of Cr, 5.7 to 6.7% by mass of Zn, 0.05% by mass or less of Ni, 0.10 to 0.16% by mass of Zr, and 0.06% by mass or less of Ti, and further contains Al. Aluminum alloy composition (3) The alloy contains Si: 0.12 mass% or less, Fe: more than 0.25 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (4) The alloy contains Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.2 to 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 to 2.9 mass%, Cr: 0.18 to 0.26 mass%, Zn: 5.1 to 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (5) 0.7% by mass<Si+Fe, Cu: 0.10% by mass or less, Mn: 0.10% by mass or less, Mg: 0.10% by mass or less, Zn: 0.8 to 1.3% by mass, and further containing Al. Aluminum alloy composition (6) The alloy contains Si: 0.12 mass% or less, Fe: more than 0.12 mass%, Cu: 2.0 to 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.05 mass% or less, and further contains Al. Aluminum alloy composition (7) Si: 0.40 mass% or less, Fe: more than 0.50 mass%, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al.
8. The hydrogen embrittlement inhibitor for aluminum alloy material according to claim 5 or 6, which can prevent hydrogen embrittlement of an aluminum alloy material having any one of the following aluminum alloy compositions (A1) to (A7). Aluminum alloy composition (A1) Si: 0.30 mass% or less, Fe: 0.35 mass% or less, Cu: 0.20 mass% or less, Mn: 0.20 to 0.70 mass%, Mg: 1.0 to 2.0 mass%, Cr: 0 .30% by mass or less, Zn: 4.0 to 5.0% by mass, V: 0.10% by mass or less, Zr: 0.25% by mass or less, Ti: 0.20% by mass or less, and further contains Al. Aluminum alloy composition (A2) Si: 0.12 mass% or less, Fe: 0.15 mass% or less, Cu: 1.5 to 2.0 mass%, Mn: 0.10 mass% or less, Mg: 2.1 to 2.6 mass%, Cr: 0.05 mass% or less, Zn: 5.7 to 6.7 mass%, Ni: 0.05 mass% or less, Zr: 0.10 to 0.16 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (A3) Si: 0.12 mass% or less, Fe: 0.15 mass% or less, Cu: 2.0 to 2.6 mass%, Mn: 0.10 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.06 mass% or less, and further contains Al. Aluminum alloy composition (A4) The alloy contains Si: 0.40 mass% or less, Fe: 0.50 mass% or less, Cu: 1.2 to 2.0 mass%, Mn: 0.30 mass% or less, Mg: 2.1 to 2.9 mass%, Cr: 0.18 to 0.26 mass%, Zn: 5.1 to 6.1 mass%, Ti: 0.20 mass% or less, and further contains Al. Aluminum alloy composition (A5) Si+Fe≦0.7 mass%, Cu: 0.10 mass% or less, Mn: 0.10 mass% or less, Mg: 0.10 mass% or less, Zn: 0.8 to 1.3 mass%, and further contains Al. Aluminum alloy composition (A6) Si: 0.12 mass% or less, Fe: 0.12 mass% or less, Cu: 2.0 to 2.6 mass%, Mn: 0.06 mass% or less, Mg: 1.9 to 2.6 mass%, Cr: 0.04 mass% or less, Zn: 5.7 to 6.7 mass%, Zr: 0.08 to 0.15 mass%, Ti: 0.05 mass% or less, and further contains Al. Aluminum alloy composition (A7) Si: 0.40 mass% or less, Fe: 0.50 mass% or less, Cu: 1.6 to 2.4 mass%, Mn: 0.30 mass% or less, Mg: 2.4 to 3.1 mass%, Cr: 0.18 to 0.28 mass%, Zn: 6.3 to 7.3 mass%, Ti: 0.20 mass% or less, and further contains Al.
Citation Information
Patent Citations
JP1973011217B1
Aluminum alloys suitable for making cans
JP1994503854A
Torque rod made of aluminum and its production
JP1998008178A
Aluminum alloy sheet for aircraft stringer excellent in stress corrosion cracking resistance and its production
JP2000212673A
Aluminum alloy material for high pressure gas vessel having excellent hydrogen embrittlement resistance
JP2009221566A